A structural equation model study on the influencing factors of sleep disorders in patients with breast cancer undergoing chemotherapy - Lu, Ting; Wei, Jiejing; Xiong, Rongsheng; Xu, Yi (Frontiers in Oncology, 2025)
ObjectiveSleep disorders are prevalent among breast cancer patients undergoing chemotherapy and are influenced by multiple psychological, social, and physiological factors. This study aims to explore the determinants of sleep disturbances in this population using a structural equation model (SEM), focusing on the role of social support, psychological distress, coping strategies, and pain.MethodsA cross-sectional study was conducted with 383 breast cancer patients undergoing chemotherapy from the Department of Oncology, the First Affiliated Hospital of Guangxi Medical University, Guangxi, China, from May 2023 to June 2024. The survey questionnaire contained a general data questionnaire and the Pittsburgh Sleep Quality Index (PSQI), Numeric Rating Scale (NRS), Simplified Coping Style Questionnaire (SCSQ), Social Support Rating Scale (SSRS), and Hospital Anxiety and Depression Scale (HADS). Structural equation modeling (SEM) was used to examine direct and indirect pathways affecting sleep quality. Model fit was assessed using CMIN/DF, RMSEA, GFI, AGFI, NFI, TLI, and CFI.ResultsThe SEM demonstrated good model fit (CMIN/DF = 2.061, RMSEA = 0.053, CFI = 0.959). Social support negatively correlated with psychological distress (β = -0.158, P = 0.013) and positively influenced sleep quality (β = -0.122, P = 0.028). Psychological distress (β = 0.567, P < 0.001) and pain (β = 0.191, P < 0.001) had significant negative effects on sleep quality. Mediation analysis confirmed that psychological distress significantly mediated the effects of social support and pain on sleep quality.ConclusionsSocial support and psychological distress are key determinants of sleep quality in breast cancer patients undergoing chemotherapy. Psychological distress mediates the relationship between pain, social support, and sleep disturbances, emphasizing the need for psychosocial interventions to improve sleep quality in this population.